Eksistensi Kelembagaan Subak dalam Konversai Lahan Sawah Tadah Hujan Menjadai Lahan Perkebunan Lada (Studi Kasus Eksistensi Kelembagaan Subak Satu di Kecamatan Mowila Kabupaten Konawe Selatan) - Mutmainnah, Mutmainnah; Nalefo, La; Isnian, Sitti Nur (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This research aims to know what the existence of Subak institution after conversions of land to a pepper plantation, how the Subak institutional function on rainfed lowland and pepper plantations. In Mowila subdistrict, Konawe Selatan district. This research was conducted in 2017 December until 2018 March. The research is qualitative by using case study approach at Subak One institution who was in Mowila Subdistrict, Konawe Selatan District. The result pointed out that the existence of Subak One institution in Mowila Subdistric still exists, the function of Subak Tri Hita Karana on rainfed rice fields that Parahyangan activity of mapagtoyo, mewiwit, ngaci, mesabe, odalan, ulun carik, the consep of tek-tek and pelampias. Pawongan with community self-help, contribution, Subak meeting, pararem and Subak coordination with government and palemahan with terraced rice field and labo. While the function of Tri Hita Karana on pepper plantation land that was. Parahyangan with odalan, ulun carik, purnma nyilem, and the ceremony moved the rice fields. Pawongan with coordination of farmers to Subak and tradition nyumbang and palemahan was characterized by two-meter land for a sacred building. The existence of Subak institution in rainfed lowland area in Tri Hita Karana activity was more complex, while the Tri Hita Karana activity on pepper plantations was simpler.